The Political Economics Side of the J-Curve - Caleiro, António (2013)
About twenty years ago, an article by van der Ploeg analysed the implications of the J-curve effect for the political business cycle in a small open economy [van der Ploeg (1989c)]. It was then shown that a sudden jump on the exchange rates in the election day should be observed if the government, in order to maximise its popularity, explores a J-curve effect. As a way of celebrating this work, that should have been more influential, it is presented in the paper a simulation study, which confirms that exchange rate overvaluation result a la van der Ploeg.